Land of Magic : South in Italian documentary cinema - Borjan, Etami (2010)
The paper focuses on ethnographic documentaries made in Italy between the 50’s and the 60’s, belonging to the so called De Martinian documentary school, synonym for a group of directors whose main interests were rituals and magical aspects of everyday life in South Italy. In that period the South was considered an exotic and unknown region or “Italian Mexico”, as the most famous Italian anthropologist Ernesto De Martino called it. Between 1959 and 1961 De Martino cooperated in the making of films mostly with Nino Dal Fra, Cecilia Mangini and Gianfranco Mingozzi, directors who portrayed traditional habits and costumes of the South such as: mourning, funeral laments, exorcist rites and other mystical and supernatural aspects. The aim of the paper is to analyze some documentaries of Luigi Di Gianni. Trance, possession rituals, superstitions, the coexistence of pagan rites and religious practices are the main topics of his films: Magia Lucana (1958), Grazia e numeri (1962), La Madonna di Pierno (1965), Il male di San Donato (1965), Il culto delle pietre (1967), Nascita di un culto (1968), La potenza degli spiriti (1968), La possessione (1971), L’attaccatura (1971), Morte e grazia (1971), La Madonna del Pollino (1971) etc.